Mobile technology consumption opportunities and challenges - Ciaramitaro, Barbara. (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2011)
"This book explores essential questions related to the cost, benefit, individual and social impact, and security risks associated with the rapid consumption of mobile technology, covering the current state of mobile technologies and their use in various domains including education, healthcare, government, entertainment, and emerging economic sectors"--Provided by publisher.